The Catholicisms of Coutances : varieties of religion in early modern France, 1350-1789 - Hayden, Michael, 1934- (McGill-Queen's studies in the history of religion., 2013)
The Catholicisms of Coutances is a richly detailed account of France from the Hundred Years' War to the French revolution. Coining the word "catholicisms" to denote the complex varieties of religious beliefs and practices within the Church, J. Michael Hayden presents a detailed analysis of the diocese of Coutances - chosen because of the unusually large number of records available - to shed light on the many ways in which religion developed and affected life in early modern France. Opening with a geographical and chronological sketch of the diocese, Hayden describes the catholicisms of mid-fourteenth century Coutances, discussing their evolution and effects over four hundred years. Employing a wide array of primary sources, the book provides a meticulous study that includes qualitative analyses of papal and diocesan documents and synodal statutes, a quantitative analysis of ordination and pastoral visit records, and a combination of both forms of analysis of the cahiers prepared for the Estates General of 1789. The Catholicisms of Coutances is an innovative contribution to contemporary understandings of Catholic beliefs and practices in the early modern period and their profound effect on the people of a diocese.